Measles and rubella immunity in the population of Bhutan, 2017 - Wangchuk, Sonam (Vaccine, 2019)
BACKGROUND: In 2017, measles elimination was verified in Bhutan, and the country appears to have sufficiently high vaccination coverage to achieve rubella elimination. However, a measles and rubella serosurvey was conducted to find if any hidden immunity gaps existed that could threaten Bhutan’s elimination status. METHODS: A nationwide, three-stage, cluster seroprevalence survey was conducted among individuals aged 1–4, 5–17, and >20 years in 2017. Demographic information and children’s vaccination history were collected, and a blood specimen was drawn. Serum was tested for measles and rubella immunoglobulin G (IgG). Frequencies, weighted proportions, and prevalence ratios for measles and rubella seropositivity were calculated by demographic and vaccination history, taking into account the study design. RESULTS: Of the 1325 individuals tested, 1045 (81%, 95% CI 78%–85%) were measles IgG seropositive, and 1290 (97%, 95% CI 95%–99%) were rubella IgG seropositive. Rubella IgG seropositivity was high in all three age strata, but only 47% of those aged 5–17 years were measles IgG seropositive. Additionally, only 41% of those aged 5–17 years who had documented receipt of two doses of measles– or measles-rubella–containing vaccine were seropositive for measles IgG, but almost all these children were rubella IgG seropositive. CONCLUSIONS: An unexpected measles immunity gap was identified among children 5–17 years of age. It is unclear why this immunity gap exists; however, it could have led to a large outbreak and threatened sustaining of measles elimination in Bhutan. Based on this finding, a mass vaccination campaign was conducted to close the immunity gap.